(untitled) (Texas Journal of Engineering and Technology, 2022)
In this article, the quality indicators of the fibers extracted from different selection varieties of cotton without ginning and under production conditions from the upper, middle and lower layers of ginning are determined. In addition, the methods of development of the cotton industry and the role of America in it are highlighted